Europe can´t figure out how to make Google pay: the AEDE canon and other initiatives on the Continent - Díaz-Noci, Javier (Anuario ThinkEPI, 2015)
During 2014, Germany and Spain reformed their copyright laws, with the specific goal of making Google news compensate newspaper publishers for the use of third parties´ copyrightable works. These reforms were based on ancillary rights in Germany, and unwaivable rights in Spain (until now reserved to moral -and therefore personal- rights). In Spain, as a direct consequence of the legal reform, Google news decided, for the first time, to stop offering its service in a specific country. These initiatives join earlier efforts, using both legal and jurisprudential approaches, to attempt to make the American giant pay, and they have caused a debate on whether or not the European Union should clarify its opinion on the matter, even though it may contradict existing legal doctrine, such as the decision about the use of hyperlinks in the Svensson case.